PRODUCT ACCESSIBILITY - Mićović, Andrej (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Article provides historical overview of the creation and development of the right to access(ibility), as well as terminological and conceptual analysis of universal design as an constitutional element of the accessibility right and finally article analyzes the rules contained in the Directive EU 2019/882 regarding: scope of the rules governing product accessibility; accessibility requirements; elements that exclude application of the accessibility requirements. From the chronological point of view, it is clear that the UN Convention on the Rights of Persons with Disabilities (CRPD) is the first binding document adopted at the international level to mention accessibility norm. However, there are ambiguities whether CRPD constitutes a new right, or complements previously established right to access. Those ambiguities are not even resolved after adoption of General Comment no. 2/2014, which strengthened the position that accessibility should not be viewed as a new right, but as a reaffirmation of the social aspect of the right to access and its conceptual upgrade.Development of the accessibility right can be fully understood through terminological and conceptual designations of environment and specifically product design. Among mutually heterogeneous terms, which are often used interchangeably with the same meaning, preference should be given to universal design, which is adopted at the international and EU level.Despite undisputed significance of the accessibility rules contained in the Directive 2019/882/EU, there are clear limitations that undermine their effect: household appliances as widely used consumer products are left out of the scope of the Directive; microenterprises accounting for 93.1% of all enterprises in the non-financial business sector are excluded from the scope of the Directive; there are provisions that allow further exemptions from the application of the accessibility requirements; deadlines for transporting Directive and respective legal measures in national legislation of Member States are disproportionally long.
Keywords: product; accessibility; requirement; universal design; obligations